DAMPAK APLIKASI MULSA DAN GENERASI UMBI BIBIT (G2, G3, LOKAL) PADA TANAMAN KENTANG (Solanum tuberosum LINN) - Ester Ruchama Jella; Agus Suryanto; Lilik Setyobudi (BUANA SAINS, 2017)
Sub-optimal environment condition and the use of low-quality seed tubers is a constraint to increase the yield of potato tubers. The purpose of this study was to determine the impact of the various applications of mulch and seed tuber G2, G3, local on growth and yield of potato tubers, as well as to temperature and soil moisture. The research was conducted in June-December, 2013 in the highlands (2232.66 m asl) in Village Ranupani, District Senduro, Lumajang, East Java Province. A randomized block design was used with a combination of treatments: without mulch (tm), black plastic mulch silver (mphp), blue plastic mulch (mpb), Chromolaena odorata mulch (mCo) and the mother bulb G2, G3, local. There are 12 combinations of treatment was repeated 3 times. The combination of these treatments consist of: tm+G2, mphp+G2, mpb+G2, mCo+G2, tm+G3, mphp+G3, mpb+G3, mCo+G3, tm+local, mphp+local, mpb+local, mCo+local. Data were analyzed using the F test with a level of 5%. If a significantly different among treatment followed by LSD test 5%. The results showed the use mphp on local seed tubers are able to provide growth and potato tubers yield optimum is 641.76 g plant-1 ( 21.39 t ha-1) compared to other treatments, but the tuber yield did not differ significantly with the use mpb in seed tubers G2.